Detection of Lgc1 Gene Low Glutelin Content in Rice Cultivars Iraq using Indel Markers - Zeina Thamer Abdul Hussein Al-Rufaye (Journal of Global Pharma Technology, 2018)
Low glutelin content rice is a good diet for patients with renal failure. Delete about a 3.5kb of a Low glutelin content Lgc1 gene sequence located in the second chromosome on the short arm between highly similar glutelin genes GluB5 andGluB4. To increase the significant, we proposed to select the adequacy in Lgc1 rice breeding, 2 molecular markers we developed to reveal the gene Lgc1, which were specified as InDel-Lgc1-2 & InDel-Lgc1-1, respectively. Our results such as The PCR results showed that band 509bp in all varieties of rice, we conclude varieties of rice in Iraq have high glutelin content. Therefore, we cannot use it for the patients with kidney failure and diabetes.Keywords:  Oryza sativa L, Lgc1 Gene, Indel Markers.